?EXTRACTION BEHAVIOUR OF COPPER LIGNOCAINE COMPLEX. Application for Determination of Lignocaine (Biological Sciences - PJSIR, 1995)
The extraction behaviour of coloured copper lignocaine complex was investigated. An organic solvent with medium dielectric constant (n-butanol) was chosen to extract the complex. A new procedure was suggested for the determination of lignocaine. It is based on the formation of coloured complex in alkaline medium (pH 10) followed by its extraction with n-butanol. The absorbance of organic.layer is measured at 570 nm. Alternatively, determination of copper content of n-butanol extract via atomic absorption spectroscopy provides an indirect method for the determina- tion of lignocaine. Both methods were applied to the analysis of pharmaceutical preparations with fair accuracy.